BGBP - A mobile application for diabetic self-management - Chew, Ke Xin (2023)
This project is a mobile application project for diabetic self-management. The mobile application will be developed through Android Studio software with Java programming language. It will provide convenience to users to record their blood glucose and blood pressure level. Besides, it is beneficial for elderly patients who always tend to forget to take medicines such as injection of insulin and pill of hypertension as there will be a reminder on medication feature implemented into the project. In order to improve the awareness of diabetes patients on the food nutrition contents especially on the sugar intake amount, food recognition technology will be implemented into this project as well. After capturing the food or selecting image of food from users’ devices, then it is able to detect and recognize the food and displaying the relevant nutrition facts such as sugar, carbohydrates, fat and so on, as well as the healthiness level of food so that users can control and plan for their diet.